Nature Trofis and Young Artist's Light Painting at Penestanan Ubud Bali - Mudana, I Wayan; Wirakesuma, I Nengah; Adi Sucipta, I Wayan; Mustika, I Ketut; Kondra, I Wayan (Syntax Corporation Indonesia, 2024)
The purpose and purpose of this research is to find out that tropical nature rich in light effects can be explored as an idea to create paintings. When he lived in Penestanan Ubud Bali in the 1957s, he taught light painting techniques that drove the birth of Young Artist-style painting. The people of Penestanan initially did not respect the painting activities offered by Arie Smit, but driven by the concern of seeing firsthand the condition of the residents of Penestanan village, who were very poor and underdeveloped, then he felt called to liberate the younger generation of the Penestanan community from poverty economically but very culturally rich. To analyze the nature of trophies and paintings of young artists in Penestanan carefully and accurately, a qualitative method is used, imperially using a participatory approach, namely analyzing the works of painters educated by Arie Smit, such as: Soki, Cakra, and Dewa Kaka using a motivational, behavioral, and interaction approach. To depict identity, aesthetic experience, creative process, until it is realized into a painting of young artists is analyzed participatory. The results and discussions in an impermatic manner describe about; (1) Tropical and Campuhan nature as inspiration for light painting, (2) Light Painters, and (3) painting forms produced by the Penestanan people of Ubud. Conclusion; The realm of trophism and light can be explored into paintings by young artists. The young artist's painting style reflects the play of colors, light, lines, and decorative. Meanwhile, perspective is used to obtain gradations and display the impression of far and near. Findings; Light painting in the West and in the East (Bali) has a very distinctive difference. The identity of Western light painting emphasizes the impression, the painter must face a direct object that gives birth to an impressionist style of painting. Meanwhile, in Young Artist's paintings, light capture displays color, decoration, and bold lines. It is arranged with a gradation game so that from perspective to get a far and close impression